CRISPR/Cas9-mediated genome editing and gene replacement in plants: Transitioning from lab to field. (November 2015) - Schaeffer, Scott M.; Nakata, Paul A.
Highlights: CRISPR/Cas9 system is becoming the preferred genome-editing tool of plant scientists. A number of new utilities, based on the CRISPR/Cas9 system, have been developed. CRISPR/Cas9 based technologies have the potential to transform crop trait improvement. Challenges and strategies to utilize CRISPR/Cas9 for crop improvement are addressed. Abstract: The CRISPR/Cas9 genome engineering system has ignited and swept through the scientific community like wildfire. Owing largely to its efficiency, specificity, and flexibility, the CRISPR/Cas9 system has quickly become the preferred genome-editing tool of plant scientists. In plants, much of the early CRISPR/Cas9 work has been limited to proof of concept and functional studies in model systems. These studies, along with those in other fields of biology, have led to the development of several utilities of CRISPR/Cas9 beyond single gene editing. Such utilities include multiplexing for inducing multiple cleavage events, controlling gene expression, and site specific transgene insertion. With much of the conceptual CRISPR/Cas9 work nearly complete, plant researchers are beginning to apply this gene editing technology for crop trait improvement. Before rational strategies can be designed to implement this technology to engineer a wide array of crops there is a need to expand the availability of crop-specific vectors, genome resources, and transformation protocols. We anticipate that these challenges will be met along with the continued evolution of the CRISPR/Cas9 system particularly in the areas of manipulation of large genomic regions, transgene-free genetic modification, development of breeding resources, discovery of gene function, and improvements upon CRISPR/Cas9 components. The CRISPR/Cas9 editing system appears poised to transform crop trait improvement.